Ketimpangan Peran Domestik Rumah Tangga dalam Cerai Gugat Pada Masyarakat Minangkabau - Almizan Almizan; Mufti Ulil Amri (Indonesian Journal of Religion and Society, 2021)
Industrialization makes people pragmatic and individualistic. The impact can be seen from the estrangement of family relations. Family ties are getting looser because each person is required to have certain duties and professions to fulfill their needs. Social transformation and deregulation make it increasingly difficult to create social intimacy. The purpose of this is to analyze the inequality of the domestic role of the household in litigation, which is more common than talak divorce, as well as social changes in family relations. The method used in this research is qualitative with descriptive approach. The research data was obtained from the results of interviews with the administrators of the Religious Courts and the people of the City/Regency in the Padang Religious High Court Region related to divorce. Other data search techniques are also carried out by means of documentation and observation to the research location. The main objective of this study is to answer one question; How is the transformation from shifting roles between husband and wife to household harmony. That the effect of social transformation on divorce is 1. increasing divorce due to nusyuz: the wife's disobedience to her husband or the wife's lack of rights and obligations. The independence of women is the main factor. 2. Increasing divorce due to shiqaq: husband and wife fighting and arguing with each other. Disharmony is the most common reason put forward by the plaintiffs. The factors that cause divorce is a form of social deviation. This study agrees with the opinion of Emile Durkheim who said that independence in life and economic level as well as the need for social deregulation in the form of deviation.